Latent Semantic Analysis - Dumais, Susan (Annual Review of Information Science and Technology (ARIST), 2003)
Presents a literature review that covers the following topics related to Latent Semantic Analysis (LSA): (1) LSA overview; (2) applications of LSA, including information retrieval (IR), information filtering, cross-language retrieval, and other IR-related LSA applications; (3) modeling human memory, including the relationship of LSA to other techniques; and (4) computational issues with LSA.